Novel germline variants in KMT2C in Chinese patients with Kleefstra syndrome-2 - Yang, Qi; Zhang, Qiang; Yi, Sheng; Zhang, Shujie; Yi, Shang; Zhou, Xunzhao; Qin, Zailong; Chen, Biyan; Luo, Jingsi (Frontiers in Neurology, 2024)
Kleefstra syndrome (KLEFS) is a rare inherited neurodevelopmental disorder characterized by intellectual disability (ID), language and motor delays, behavioral abnormalities, abnormal facial appearance, and other variable clinical features. KLEFS is subdivided into 2 subtypes: Kleefstra syndrome-1 (KLEFS1, OMIM: 610253) caused by a heterozygous microdeletion encompassing EHMT1 on chromosome 9q34.3 or pathogenic variants in the Euchromatic Histone Lysine Methyltransferase 1 (EHMT1) gene, and Kleefstra syndrome-2 (KLEFS2, OMIM: 617768) caused by pathogenic variants in the KMT2C gene. More than 100 cases of KLEFS1 have been reported with pathogenic variants in EHMT1 gene. However, only 13 patients with KLEFS2 have been reported so far. In the present study, five unrelated chinese patients were diagnosed with KLEFS2 caused by KMT2C variants through whole-exome-sequencing (WES). We identified five different variants of the KMT2C gene in these patients: c.9166C>T(p.Gln3056*), c.9232_9247delCAGCGATCAGAACCGT(p.Gln3078fs*13), c.5068dupA(p.Arg1690fs*10), c.10815_10819delAAGAA(p.Lys3605fs*7) and c.6911_6912insA(p.Met2304fs*8). All five patients had a clinical profile similar to that patients with KLEFS2. To analyze the correlation between KLEFS2 genotype and phenotype, we examined 18 variants and their associated phenotypes in 18 patients with KLEFS2. Patients carrying KMT2C variants presented with a wide range of phenotypic defects and an extremely variable phenotype. We concluded that the core phenotypes associated with KMT2C variants were intellectual disability, facial dysmorphisms, language and motor delays, behavioral abnormalities, hypotonia, short stature and weight loss. Additionally, sex may be one factor influencing the outcome. Our findings expand the phenotypic and genetic spectrum of KLEFS2 and help to clarify the genotype-phenotype correlation.